Computational modal analysis on finite element model of body-in-white structure and its correlation with experimental data - N. A. Z., Abdullah; M. S. M., Fouzi; M. S. M., Sani (Universiti Malaysia Pahang, 2020)
Nowadays, computational modelling and simulation are highly popular to increase the efficiency, productivity and shorten the product development period. The quality of a structure also can be determined by using computational analysis such as finite element analysis. Body-in-white structure, as one of the most important structures in the automotive field, has gained a lot of interest as the topic of research. This increase the demand of having a good finite element model of the structure. However, since body-in-white is a highly complicated structure, sometimes modelling simplification cannot be avoided. This study intended to investigate the level of accuracy of the simplified body-in-white model that was modelled by using several modelling strategies. The first body-in-white finite element model was modelled by neglecting the existing joint element in its actual structure. The other body-in-white model includes the joint element by including two different one-dimensional elements to replicate the joining in BIW actual structure. Validation on these body-in-white models are performed by correlating the finite element modal properties with the experimental modal properties. The discrepancies that had surfaced after the correlation was reduced by using a model updating method. The discussed results showed that as the model is under major simplification, several parameters were inaccurately assumed in the initial body-in-white model. Thus, the model updating method has successfully determined the less accurate parameter and the level of discrepancies between the model and experimental data were successfully reduced.